Enterpreneurship and innovation activites in the schumpeterian lines - George Korres; Emmanuel Marmaras; George Tsobanoglou (European Regional Science Association (ERSA), 2004)
The importance of diffusion of technology for economic growth has been emphasised by economic literature. Much of the recent work on economic growth can be viewed as refining the basic economic insights of classical economists. The recent debate on the determinants of output growth has concentrated mainly on the role of knowledge, typically produced by a specific sector of the economy, and furthermore in the role of entrepreneurship and the implications on economic growth. This paper attempts to examine the role of entrepreneurship, and those of innovation activities (technical change, research and development and diffusion of technology) and the effects of output growth, according to the Schumpeterian lines. Following on the Schumpeterian tradition, this paper starts from the recognition that there are two main patterns of innovations: the first one is the creative destruction pattern and the second one is a creative accumulation pattern. Also, it emphasizes the role of entrepreneurship and the impact of the diffusion of technology in the inter-country and international economic contexts using some of the empirical implementation of epidemic, probit analysis and moreover from technological substitution models. Key Words: Entrepreneurship, Innovation Activities, Diffusion, Modernization, Competitiveness, Schumperer.
Keywords: 330; Entrepreneurship; Innovation Activities; Diffusion; Modernization; Competitiveness; Schumperer